Regulation of photosynthesis and ROS homeostasis by Fd1 and FNR1 confers thermotolerant yield stability in rice - Qiaoyan Wang; Qingmei Su; Man Li; Dongdong Chen; Yuchun Rao; Pengfei Dong; Bingxin Ye; Tingyi Wang; Zhiqi Hao; Rui Pang; Ruiying Li; Guangheng Zhang; et al. (Science Bulletin, 2026)

The potential mechanism of nitrous oxide accumulation in wastewater treatment plants under different load conditions - Wen-Jiao Sang; Bing Gong; Chong-Yang Xing; Bei-Bei Chen; Zhi-Lin Zhang; Hui-Min Fu; Ya-Song Chen; Wan Sun; Meng-Meng Liu; Shun-Li Cheng; Yu-Lin Wang; Qiang Wang; et al. (International Biodeterioration & Biodegradation, 2026)

Pharmacological effect of rhCC16 on COPD: anti-senescence via the PI3K-AKT-mTOR pathway - Rui Gao; Shuo Wu; Chu-lin Zhang; Chao-feng Liu; Ting Li; Min Guo; Zhao-yang Chen; Hai-long Wang; Min Pang (Molecular and Cellular Biochemistry, 2026)

SYVN1-provoked RASA1 ubiquitination promotes pulmonary inflammation in chronic obstructive pulmonary disease - Ju-Hong Wu; Yi-Cheng Ma; Yu-Qi Wang; Hai-Long Miao; Meng-Xue Liu; Dong-Xu Hua; Min-Min Tang; Tian-Rui Sui; Zhi-Yong Wu; Yu Wang; Jin Yang; Hui Zhao; et al. (Inflammation Research, 2026)

Sinomenine ameliorates experimental autoimmune neuritis by suppressing pro-inflammatory immune components and restoring immune balance - Yan-Mei Gong; Zhen-Lin Liu; Si-Miao Li; Yi-Fan Wei; Guo-Hui Gao; Rui-Qi Xu; Xue-Min Li; Yu-Dong Liu; Rui-Sheng Duan; Ying Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Quantitative study on the cave environmental factors for the fractionation of stable oxygen isotopes during the deposition of speleothem - Yue Jin; Chun-Jie Wang; Jian Zhang; Wen-Jun Sun; Chao-Jun Chen; Yao Wu; Hua-Yan Li; Yue-Hua Xiang; Yue-Yuan Lin; Xin-Rui Ye; Xin-Yan Li; Zhong-Lin Deng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

High-value utilization of chromium ore processing residue (COPR) through corn straw-soda roasting followed leaching processes - Cheng Tian; Zilong Li; Cunfang Lu; Rui Xu; Min Zhang; Lin Yang; Wenlin Xie; Zhengnan Zhong; Yuanyuan He; Juan Wen; Dan Luo (Journal of Environmental Chemical Engineering, 2026)

Modeling and experimental validation of crack-induced bottom-side erosion effects in buried pipelines - Yan-Ning Wang; Tai-Kai Li; Jing-Rui Peng; Xin-Hao Min; Lin-Shuang Zhao (Tunnelling and Underground Space Technology, 2026)

Synergistic recovering Fe, Al and biochar through biomass-reduction alkali roasting and wet magnetic separation for red mud (RM): behavior and mechanism - Rui Xu; Cunfang Lu; Min Zhang; Cheng Tian; Dan Luo; Lin Yang; Wenlin Xie; Zhengnan Zhong; Juan Wen (Minerals Engineering, 2026)

Encoding intrinsic rare-earth dissolution selectivity into deep eutectic solvents via coordination-active functional group design - Zhihan Zhang; Guobiao Li; Zhi Wang; Wanhai Xiao; Yong Lin; Shuping Cheng; Rui Min; Jian Wu; Mingqing Liu; Dong Wang (Journal of Cleaner Production, 2026)

Body size- and water homeostasis-dependent temperature stress tolerance and transcriptional changes in red fire ant workers - Wei Gao; Rui Peng; Jian-min Yang; Jian-lin Lu; Hong-yun Cao; Ying-huan Li; Chun Li; Wen Fu; Jin Xu (Journal of Asia-Pacific Entomology, 2026)

Bioaccumulation and trophic transfer of phthalate esters in mangrove food web - Jianan Liu; Yuyan Liu; Siwen Chen; Rui Xu; Haofeng Liu; Zefeng Wang; Xianbiao Lin; Ye Li; Min Liu (Marine Pollution Bulletin, 2026)

The association of co-exposure to polycyclic aromatic hydrocarbons and phthalates with surrogate indicators of insulin resistance: a panel study - Sha You; Lin Liu; Min Xiang; Lei Zhao; Wenting Guo; Xiaomin Zhang; Rui Zhu; Liangle Yang (Environmental Geochemistry and Health, 2026)

Peripheral inflammation in spinocerebellar ataxia type 3: associations with genetic and clinical manifestations - Jia-Yi Zhang; Qiu-Ni Su; Han Lin; Wei Lin; Mao-Lin Cui; Zhuo-Ying Huang; Bei-Ning Ye; Ying-Xin Ye; Yi-Lin Jia; Qing-Ying Zhu; Zhi-Han Li; Min-Ting Lin; et al. (Inflammation Research, 2025)

Morphology and nutrient content of bamboo rhizomes: Responses to enclosure succession in a Phyllostachys edulis forest in Wuyi Mountains, China - Xing Cai; Rui Cheng; Zhenhua Chen; Jiannan Lin; Min Wu; Jiaying Liu; Jihong Xiao; Yuchen Lin; Lingyan Chen; Yirong Zhang; Jundong Rong; Tianyou He; et al. (Forest Ecology and Management, 2025)

Sequential targeted nanomedicine MPC treats cerebral ischemia-reperfusion injury via neuronal microenvironment reprogramming - Shuya Wang; Ruishi Li; Xiaojing Shi; Tingli Xiong; Wenxuan Zheng; Weimin Qi; Min Liu; Lin Dai; Qian Lin; Rui Huang; Wei Dai; Min Zhou; et al. (Chemical Engineering Journal, 2025)

Effect of low-energy stirring temperature on the formation of oil-in-water emulsions stabilized by gelatin-arginine complexes - Jun Qi; Yu-cong Li; Hui-min Yan; Li-ting Zeng; Ao-jing Lv; Rui-ling Dong; Xue-qing Li; Zhou Lin; Le-le Shao; Lang Zhang; Guo-qing Duan; Chun-hui Zhang; et al. (Food Research International, 2025)

Ultra-long and rapid operating zinc metal batteries enabled by multifunctional polarizable interface stabilizer - Song-Lin Tian; Li Lin; Si-Yu Jiang; Li-Na Song; Hai-Rui Wang; Ping Nie; Li-Min Chang; Wan-Qiang Liu (Chemical Engineering Journal, 2025)

A 3D-printed chitosan-based pH-responsive dual functional scaffold for osteomyelitis: synergistic antibacterial and osteogenic treatment - Mingyue Lin; Yijing Stehle; Li Chen; Mao Yang; Ke Zeng; Chenxin Wang; Rui Zhang; Huanshuo Zhang; Jiehui Yang; Denglang Hu; Min Huang; Yubao Li; et al. (Carbohydrate Polymers, 2025)

Engineering a recombinant VP2-Based neutralizing epitope vaccine candidate against canine parvovirus: a preliminary immunogenicity assessment - Qing Wu; Yuhan Jin; Weiyue Cao; Zeheng Ren; Xinyu Li; Zhitong Li; Jiachi Han; Chunxu Shi; Rui Gao; Min Yan; Shengrui Zhu; Wenpeng Guan; et al. (Veterinary Research Communications, 2025)

Fire ant-inspired bone repair breakthrough: Self-assembly strategy of microspheres driven by physical hydrogen bonding and hydrophobic interactions - Rui Zhang; Yijing Stehle; Li Chen; Ke Zeng; Mingyue Lin; Chenxin Wang; Huanshuo Zhang; Jiehui Yang; Denglang Hu; Min Huang; Mao Yang; Yubao Li; et al. (Chemical Engineering Journal, 2025)

Oil Film Detection for Marine Radar Image Using SBR Feature and Adaptive Threshold - Yulong Yang; Jin Yan; Jin Xu; Xinqi Zhong; Yumiao Huang; Jianxun Rui; Min Cheng; Yuanyuan Huang; Yimeng Wang; Tao Liang; Zisen Lin; Peng Liu (Journal of Marine Science and Engineering, 2025)
Marine oil spills pose a serious and persistent threat to marine ecosystems, coastal resources, and global environmental health. These incidents not only disrupt ecological balance by damaging marine flora and fauna but also lead to long-term economic consequences for fisheries, tourism, and maritime industries. Owing to their rapid spread and often unpredictable occurrence, timely and accurate detection is essential for effective containment and mitigation. An efficient detection system can significantly enhance the responsiveness of emergency teams, enabling targeted interventions that minimize ecological damage and economic loss. This paper proposes a marine radar-based oil spill detection method that combines the Significance-to-Boundary Ratio (SBR) feature with an improved Sauvola adaptive thresholding algorithm. The raw radar data was firstly preprocessed through mean and median filtering, grayscale correction, and contrast enhancement. SBR features were then employed to extract coarse oil spill regions, which were further refined using an improved Sauvola thresholding algorithm followed by a denoising step to obtain fine-grained segmentation. Comparative experiments using different threshold values demonstrate that the proposed method achieves superior segmentation performance by better preserving oil spill boundaries and reducing background noise. Overall, the approach provides a robust and efficient solution for marine oil spill detection and monitoring.

miR-758-3p Interferes with Neuronal Apoptosis in Cerebral Ischemia–Reperfusion by Inhibiting ILK - Xiaoli Min; Xuesong Bai; Qing Zhao; Wenwu Yang; Sixian Lin; Lei Xian; Rui Jing; Xuhui Li; Wenji Jia; Wei Miao; Mei Yin; Feifei Shang; et al. (Molecular Neurobiology, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Toward safe rice production in As-Cd co-contaminated paddy soils: Biogeochemical mechanisms and remediation strategies - Jing-Min Yang; Hui-Lin Chen; Xin Wang; Dong-Xing Guan; Xiong-Hui Ji; Yun-He Xie; Rui Huang; Bo Peng; Qin-Bo Qin (Critical Reviews in Environmental Science and Technology, 2025)

A multirisk-rescued biomimetic nanozyme against periodontitis via inflammation targeting and microenvironment reprogramming - Lin Li; Rui-Xin Wu; Jia Wang; Rui Jin; Xin-Yu Zhang; Mei Xu; Si-Yao Li; Rui Gao; Bei-Min Tian; Xiao-Tao He; Fa-Ming Chen; Yuan Yin (Chemical Engineering Journal, 2025)

Selective regulation of products for guaiacol hydrodeoxygenation by adjusting type and acidity of supports - Min Lin; Daxin Jiang; Yuhao Yan; Lulu Zhan; Xianliang Song; Rui Li; Yulong Wu (Bioresource Technology, 2024)

Muscone inhibits angiotensin II–induced cardiac hypertrophy through the STAT3, MAPK and TGF-β/SMAD signaling pathways - Yi-jiang Liu; Jia-jia Xu; Cui Yang; Yan-lin Li; Min-wei Chen; Shi-xiao Liu; Xiang-hui Zheng; Ping Luo; Rui Li; Di Xiao; Zhong-gui Shan (Molecular Biology Reports, 2024)
Background Muscone is a chemical monomer derived from musk. Although many studies have confirmed the cardioprotective effects of muscone, the effects of muscone on cardiac hypertrophy and its potential mechanisms are unclear.The aim of the present study was to investigate the effect of muscone on angiotensin (Ang) II-induced cardiac hypertrophy. Methods and results In the present study, we found for the first time that muscone exerted inhibitory effects on Ang II-induced cardiac hypertrophy and cardiac injury in mice. Cardiac function was analyzed by echocardiography measurement, and the degree of cardiac fibrosis was determined by the quantitative real-time polymerase chain reaction (qRT-PCR), Masson trichrome staining and western blot assay. Secondly, qRT-PCR experiment showed that muscone attenuated cardiac injury by reducing the secretion of pro-inflammatory cytokines and promoting the secretion of anti-inflammatory cytokines. Moreover, western blot analysis found that muscone exerted cardio-protective effects by inhibiting phosphorylation of key proteins in the STAT3, MAPK and TGF-β/SMAD pathways. In addition, CCK-8 and determination of serum biochemical indexes showed that no significant toxicity or side effects of muscone on normal cells and organs. Conclusions Muscone could attenuate Ang II-induced cardiac hypertrophy, in part, by inhibiting the STAT3, MAPK, and TGF-β/SMAD signaling pathways.

Corrigendum to “Euphpepluone S, a new lathyrane diterpenoid with anti-inflammatory activity from Euphorbia peplus L.” [Phytochem. Lett. 55 2023, 61–66] - Shi-Peng Guan; Ying Yang; Mao Sun; Min Cai; Xue-Xue Pu; Jian-Yi Huang; Ping Yi; Lin Liu; Ming-Rui Yuan; Yuan-Yuan Cheng; Ying-Tong Di (Phytochemistry Letters, 2024)

Strong absorption of silica over full solar spectrum boosted by interfacial junctions and light–heat–storage of Mg(OH)2–(CrOx–SiO2) - Rui-Min Hao; Lin Zhu; Teng-Fei Shang; Zhi-Bin Xu; Qin-Pei Wu (Chemical Engineering Journal, 2024)

Natural aromatic extract of black tea improved the water retention of pork meat batter - Wen-ping Xu; Rui-ling Dong; Ao-jing Lv; Yu-cong Li; Li-ting Zeng; Xue-ling Gao; Jun Qi; Zhou Lin; Hui-min Yan; Chun-hui Zhang; Guo-yuan Xiong (Food Research International, 2024)

Stefin B alleviates the gouty arthritis in mice by inducing the M2 polarization of macrophages - Shishui Lin; Xu Hu; Yang Li; Jiyue Huang; Rui Zhang; Xinxin Bai; Shaohuang Weng; Min Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
The present study aims to explore the therapeutic effect of Stefin B on gouty arthritis (GA) and the polarization of macrophages in mice. Stefin B-overexpressed or knockdown M0 macrophages were constructed. The GA model was established in mice by injecting 25 mg/mL MSU, followed by a single injecting of Stefin B-overexpressing adenovirus vector (GA model + Stefin B OE) or an empty vector (GA model + Stefin B OE NC). Stefin B was found lowly expressed in M1 macrophages. CD206 was markedly upregulated and IL-10 release was signally increased in Stefin B-overexpressed macrophages. In gouty arthritis mice, marked redness and swelling were observed in the ankle joint. Dramatical infiltration of inflammatory cells was observed in the GA model and GA model + Stefin B OE NC groups, which was suppressed in the Stefin B OE group. Increased proportion of F4/80 + CD86 + cells observed in GA mice was markedly repressed by Stefin B overexpression, accompanied by the declined level of Caspase-1 and IL-17. Collectively, Stefin B alleviated the GA in mice by inducing the M2 polarization of macrophages.

Catalytic aqueous hydrodeoxygenation of palmitic acid with in-situ hydrogen donor - Xiaoxian Li; Min Lin; Rui Li; Mingde Yang; Yulong Wu (Fuel, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

A study on the decision-making mechanism and promotion policy of urban residents’ domestic waste-classification behavior: evidence from Sichuan province - Qianyu Dong; Rui Yan; Runli Xiong; Weikai Xie; Min Pang; Lin Liang (Environment, Development and Sustainability, 2024)

Study of life cycle assessment: Transforming microalgae to biofuel through hydrothermal liquefaction and upgrading in organic or aqueous medium - Shaomin Zhou; Min Lin; Xi Zhang; Lulu Zhan; Rui Li; Yulong Wu (Journal of Cleaner Production, 2024)

Characterization of key flavor substances and their microbial sources in traditional sour bamboo shoots - Hui Tang; Jin-Kui Ma; Lin Chen; Li-Wen Jiang; Lin-Zhi Kang; Ying-Yu Guo; Ge-Yang Men; Dan-Xia Nie; Rui-Min Zhong (Food Chemistry, 2024)

Temperature–Controlled hydrothermal hydrogenation of palmitic acid to alkanol or alkanes over Co@CN–x catalysts derived from ZIF–67 - Min Lin; Daxin Jiang; Yuhao Yan; Xiaoxian Li; Lulu zhan; Xianliang Song; Rui Li; Yulong Wu (Chemical Engineering Journal, 2024)

GW4064 inhibits migration and invasion through cathepsin B and MMP2 downregulation in human bladder cancer - Chien-Chang Kao; Chien-Rui Lai; Yi-Hsuan Lin; Tzu-Min Chen; Yu-Ling Tsai; Wen-Chiuan Tsai; Tze-Yun Ong; Hisao-Hsien Wang; Sheng-Tang Wu; Ying Chen (Chemico-Biological Interactions, 2024)

Integrating photovoltaic noise barriers and electric vehicle charging stations for sustainable city transportation - Kai Zhang; Min Chen; Rui Zhu; Fan Zhang; Teng Zhong; Jian Lin; Linlin You; Guonian Lü; Jinyue Yan (Sustainable Cities and Society, 2024)

Comparison of demineralized bone matrix with different cycling crushing times in posterolateral fusion model of athymic rats - Shao-Lin Ji; Xiao-Dan Zhao; Li-Min Wang; Cheng-Gang Pang; Wen-Jing Li; Kun-Xiu Song; Rong-Xing Ma; Rui-Feng Li; Jing-Yu Zhang; Yong-Cheng Hu (Cell and Tissue Banking, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Insights into influence of CeO2 crystal structure effects on hydrothermal hydrogenation for palmitic acid over Ni/CeO2 catalysts - Min Lin; Yuhao Yan; Daxin Jiang; Xiaoxian Li; Rui Li; Yulong Wu (Chemical Engineering Journal, 2023)

Rethinking personal carbon trading (PCT) mechanism: A comprehensive review - Yun-En Tang; Ru Fan; Ang-Zu Cai; Le-Yi Wang; Rui-Min Lin; Xiang-Zhou Meng; Ling Chen; Ru Guo (Journal of Environmental Management, 2023)

Hydrothermal stable Ni nanoparticles encapsulated in carbon for hydrothermal hydrogenation of long-chain fatty acids to alkanes - Min Lin; Xiaoxian Li; Yuhao Yan; Rui Li; Yulong Wu (Chemical Engineering Journal, 2023)

Moringa oleifera Lam. leaves as new raw food material: A review of its nutritional composition, functional properties, and comprehensive application - Min Yang; Liang Tao; Xin-Rui Kang; Zi-Lin Wang; Ling-Yan Su; Ling-Fei Li; Fan Gu; Cun-Chao Zhao; Jun Sheng; Yang Tian (Trends in Food Science & Technology, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Single-stage object detector with local binary pattern for remote sensing images - Kexue Zhou; Min Zhang; Sheng Lin; Rui Zhang; Hai Wang (International Journal of Remote Sensing, 2023)

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

Short-term effects of individual exposure to PM2.5 on hospital admissions for myocardial infarction and stroke: a population-based case-crossover study in Guangzhou, China - Jie-Qi Jin; Guo-Zhen Lin; Shuang-Ying Wu; Mu-Rui Zheng; Hui Liu; Xiang-Yi Liu; Min-Qian Yan; Zhao-Yue Chen; Chun-Quan Ou (Environmental Science and Pollution Research, 2023)

Euphpepluone S, a new lathyrane diterpenoid with anti-inflammatory activity from Euphorbia peplus L. - Shi-Peng Guan; Ying Yang; Mao Sun; Min Cai; Xue-Xue Pu; Jian-Yi Huang; Ping Yi; Lin Liu; Ming-Rui Yuan; Yuan-Yuan Cheng; Ying-Tong Di (Phytochemistry Letters, 2023)

PcCLCg is involved in the accumulation of Cl− in shoots for osmotic adjustment and salinity resistance in the Cl−-tolerant xerophyte Pugionium cornutum - Yan-Nong Cui; Zi-Ru Lin; Mei-Mei Cai; Rui-Wen Liu; Suo-Min Wang; Qing Ma (Plant and Soil, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Future land-use change and its impact on terrestrial ecosystem carbon pool evolution along the Silk Road under SDG scenarios - Min Cao; Ya Tian; Kai Wu; Min Chen; Yu Chen; Xue Hu; Zhongchang Sun; Lijun Zuo; Jian Lin; Lei Luo; Rui Zhu; Zhenci Xu; et al. (Science Bulletin, 2023)

Infant food production environments: A potential reservoir for vancomycin-resistant enterococci non-nosocomial infections - Zining Wang; Sihao Liao; Guanwen Huang; Mengyao Feng; Rui Yin; Lin Teng; Chenghao Jia; Yicheng Yao; Min Yue; Yan Li (International Journal of Food Microbiology, 2023)

Unique bacterial communities and lifestyles in deep ocean blue holes: Insights from the Yongle Blue Hole (South China Sea) - Shun Zhou; Jiwen Liu; Peng Yao; Liang Fu; Zuosheng Yang; Yulin Zhang; Rui Du; Chao Jia; Lin Chen; Jinchang Liang; Xiaolei Wang; Xiaochong Shi; et al. (Frontiers in Marine Science, 2023)
Deep ocean blue holes possess steep physicochemical gradients, especially low dissolved oxygen concentration, which shape the extraordinary microbial communities. However, the environmental responses of microorganisms with different lifestyles and knowledge of culturable microorganisms in the blue holes are still unknown. Here, we investigated the bacterial community structure with different lifestyles of the world’s deepest blue hole - the Yongle Blue Hole (YBH) in the South China Sea using both culture-dependent and -independent methods. YBH can be divided by oxygen content into an oxic zone, a suboxic zone and two anoxic zones. The abundance of bacteria, archaea, genes dsrB and soxB were all higher in the free-living (FL) lifestyle than in the particle-associated (PA) lifestyle, yet the diversity and richness of PA bacteria were higher than that of FL bacteria. More Gammaproteobacteria and less Alphaproteobacteria , Chloroflexi and Nitrospinae were observed within the FL fraction than within the PA fraction. The relative abundance of sulfur-oxidizing bacteria (SOB) was dominant between 100-140 m (anoxic zone I) in YBH, with a maximum of 90.0% (140 m FL fraction). The SOB in YBH were mainly colorless sulfur bacteria and purple non-sulfur bacteria, of which Thiomicrorhabdus and Sulfurimonas were the main representatives. In addition, a total of 294 bacterial strains were isolated on a variety of media and culture conditions, and 22.2% (18/81) of anaerobic strains were identified as potential novel species. Our study reveals a distinction between FL and PA bacteria in YBH. It contributes to further understanding of the bacterial community in deep ocean blue holes, and provides bacterial resources for subsequent studies on their adaptation to extreme marine environments.

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Preparation of Metal-Acid bifunctional catalyst Ni/ZSM-22 for palmitic acid catalytic deoxygenation - Xiaoxian Li; Min Lin; Rui Li; Qiang Lu; Mingde Yang; Yulong Wu (Fuel, 2023)

ACC deaminase-encoding Pseudomonas putida arrests seed germination: an alternative strategy for grass and weed control - Di Zhou; Jia-Ling Zhao; Rui Wang; Hai-Lin Wang; Daniela D. Herrera-Balandrano; Tang-Min Chen; Xiao-Feng Lu; Xu-Chu Duan; Mahdi Shahriar; Xin-Chi Shi; Pedro Laborda; Su-Yan Wang (Plant and Soil, 2022)

Selenium-Alleviated Testicular Toxicity by Modulating Inflammation, Heat Shock Response, and Autophagy Under Oxidative Stress in Lead-Treated Chickens - Size Wang; Lulu Hou; Min Wang; Rui Feng; Xu Lin; Shifeng Pan; Qian Zhao; He Huang (Biological Trace Element Research, 2021)

Present in-situ stress distribution characteristics of strike-slip in SH Oilfield, Tarim Basin - Teng Zhao; Wenge Hu; Rui Zhao; Min Yang; Qiang Wang; Huixi Lin; Zhixing Ru; Dian Bao; Fei Cao (Arabian Journal of Geosciences, 2021)

Experimental and numerical study on the fragmentation mechanism of a single calcareous sand particle under normal compression - Du-min Kuang; Zhi-lin Long; Rui-qi Guo; Tao Zhao; Kai Wu (Bulletin of Engineering Geology and the Environment, 2021)

Identification and expression analysis of caffeoyl-coenzyme A O-methyltransferase family genes related to lignin biosynthesis in tea plant (Camellia sinensis) - Shi-Jia Lin; Ya-Zhuo Yang; Rui-Min Teng; Hao Liu; Hui Li; Jing Zhuang (Protoplasma, 2021)

Effects of shading on lignin biosynthesis in the leaf of tea plant (Camellia sinensis (L.) O. Kuntze) - Rui-Min Teng; Yong-Xin Wang; Hui Li; Shi-Jia Lin; Hao Liu; Jing Zhuang (Molecular Genetics and Genomics, 2021)

Gastrointestinal involvement of COVID-19 and potential faecal transmission of SARS-CoV-2 - Min Song; Zong-lin Li; Ye-jiang Zhou; Gang Tian; Ting Ye; Zhang-rui Zeng; Jian Deng; Hong Wan; Qing Li; Jin-bo Liu (Journal of Zhejiang University-SCIENCE B, 2020)

Hirsutella sinensis inhibits NLRP3 inflammasome activation to block aristolochic acid-induced renal tubular epithelial cell transdifferentiation - Min Yu; Yu-lin Man; Meng-hua Chen; Li-hua Wu; Yi Zhou; Xiao-ling Zhou; Na Chen; Rui Ma; Li-na Sun (Human Cell, 2020)

Association Between Body Mass Index and Disease Severity in Chinese Spinocerebellar Ataxia Type 3 Patients - Jin-Shan Yang; Ping-Ping Chen; Min-Ting Lin; Mei-Zhen Qian; Hui-Xia Lin; Xiao-Ping Chen; Xian-Jin Shang; Dan-Ni Wang; Yu-Chao Chen; Bin Jiang; Yi-Jun Chen; Ning Wang; et al. (The Cerebellum, 2018)

Overexpression of Nogo receptor 3 (NgR3) correlates with poor prognosis and contributes to the migration of epithelial cells of nasopharyngeal carcinoma patients - Jiang-Yi He; Ping Han; Yu Zhang; Yong-Dong Liu; Shi-Jian Song; Guo-Kai Feng; Yu An; Ai-Jun Zhou; Hong-Bo Wang; Li Yuan; Zhi-Rui Lin; Tian-Liang Xia; et al. (Journal of Molecular Medicine, 2018)

Improved salt tolerance of medicinal plant Codonopsis pilosula by Bacillus amyloliquefaciens GB03 - Qing-Qing Han; Yong-Na Wu; Hui-Juan Gao; Rui Xu; Paul W. Paré; Huazhong Shi; Qi Zhao; Hui-Ru Li; Sardar Ali Khan; Yin-Quan Wang; Suo-Min Wang; Jin-Lin Zhang (Acta Physiologiae Plantarum, 2017)

Improvement of soybean transformation via Agrobacterium tumefaciens methods involving α-aminooxyacetic acid and sonication treatments enlightened by gene expression profile analysis - Yan-Min Zhang; Zi-Hui Liu; Rui-Juan Yang; Guo-Liang Li; Xiu-Lin Guo; Hua-Ning Zhang; Hong-Mei Zhang; Rui Di; Qing-Song Zhao; Meng-Chen Zhang (Plant Cell Reports, 2016)

A retrospective study of the occurrence of ischemic-type biliary lesions post liver transplantation - Rui Shi; Ya-Min Zhang; Yong-Lin Deng; Hong Zheng; Cheng Pan; Zhong-Yang Shen (Science China Life Sciences, 2016)

Notch2 signaling contributes to cell growth, invasion, and migration in salivary adenoid cystic carcinoma - Jing Qu; Min Song; Jian Xie; Xiao-Yu Huang; Xiao-Meng Hu; Rui-Huan Gan; Yong Zhao; Li-Song Lin; Jiang Chen; Xu Lin; Da-Li Zheng; You-Guang Lu (Molecular and Cellular Biochemistry, 2016)

Clinical, biochemical, neuroimaging and molecular findings of X-linked Adrenoleukodystrophy patients in South China - Min-yan Jiang; Yan-na Cai; Cui-li Liang; Min-zhi Peng; Hui-ying Sheng; Li-ping Fan; Rui-zhu Lin; Hua Jiang; Yonglan Huang; Li Liu (Metabolic Brain Disease, 2015)

α7nAChR is expressed in satellite cells at different myogenic status during skeletal muscle wound healing in rats - Zhi-Ling Tian; Shu-Kun Jiang; Miao Zhang; Meng Wang; Jiao-Yong Li; Rui Zhao; Lin-Lin Wang; Min Liu; Shan-Shan Li; Meng-Zhou Zhang; Da-Wei Guan (Journal of Molecular Histology, 2015)

New Perspectives on Dietary-derived Treatments and Food Safety—Antinomy in a New Era - Si-Yuan Pan; Si-Hua Gao; Rui-Chao Lin; Shu-Feng Zhou; Hong-Guan Dong; Min-Ke Tang; Zhi-Ling Yu; Kam-Ming Ko (Critical Reviews in Food Science and Nutrition, 2015)

Low Bone Mass is Associated with Stroke in Chinese Postmenopausal Women: The Chongqing Osteoporosis Study - Rui Zhou; Dong Liu; Rui Li; Shiming Zhou; Min Cui; Lin Chen; Huadong Zhou (Cell Biochemistry and Biophysics, 2015)

New isoflavones with cytotoxic activity from the rhizomes of Iris germanica L. - Guo-Yong Xie; Xiao-Ying Qin; Rui Liu; Qi Wang; Bin-Bin Lin; Guo-Kai Wang; Guang-Kai Xu; Rui Wen; Min-Jian Qin (Natural Product Research, 2013)

The N-glycoform of sRAGE is the key determinant for its therapeutic efficacy to attenuate injury-elicited arterial inflammation and neointimal growth - Hyun-Jin Tae; Ji Min Kim; Sungha Park; Noboru Tomiya; Geng Li; Wen Wei; Natalia Petrashevskaya; Ismayil Ahmet; John Pang; Stefanie Cruschwitz; Rebecca A. Riebe; Yinghua Zhang; et al. (Journal of Molecular Medicine, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Erbin inhibits TGF-β1-induced EMT in renal tubular epithelial cells through an ERK-dependent pathway - Qiaodan Zhou; Rui Zeng; Chuou Xu; Lili Liu; Lin Chen; Pei Kou; Guangchang Pei; Shoujun Bai; Yamin Zhang; Caixia Li; Song Rong; Min Han; et al. (Journal of Molecular Medicine, 2012)

Dew water isotopic ratios and their relationships to ecosystem water pools and fluxes in a cropland and a grassland in China - Xue-Fa Wen; Xuhui Lee; Xiao-Min Sun; Jian-Lin Wang; Zhong-Min Hu; Sheng-Gong Li; Gui-Rui Yu (Oecologia, 2012)

Higher rates of nitrogen fertilization decrease soil enzyme activities, microbial functional diversity and nitrification capacity in a Chinese polytunnel greenhouse vegetable land - Weishou Shen; Xiangui Lin; Weiming Shi; Ju Min; Nan Gao; Huayong Zhang; Rui Yin; Xinhua He (Plant and Soil, 2010)

Molecular phylogeny of Ranunculaceae based on rbc L sequences - Ying-fan Cai; Sheng-wei Li; Min Chen; Ming-feng Jiang; Yi Liu; Yong-fang Xie; Quan Sun; Huai-zhong Jiang; Neng-wen Yin; Ling Wang; Rui Zhang; Cheng-lin Huang; et al. (Biologia, 2010)

Involvement of the ornithine decarboxylase/polyamine system in precondition-induced cardioprotection through an interaction with PKC in rat hearts - Ya-Jun Zhao; Wei-Hua Zhang; Chang-Qing Xu; Hong-Zhu Li; Li-Na Wang; Hong Li; Yi-Hua Sun; Yan Lin; Li-Ping Han; Li Zhang; Yie Tian; Rui Wang; et al. (Molecular and Cellular Biochemistry, 2009)

A novel triple-regulated oncolytic adenovirus carrying PDCD5 gene exerts potent antitumor efficacy on common human leukemic cell lines - Min Xie; Ji-Hong Niu; Yan Chang; Qi-Jun Qian; Hong-Ping Wu; Lin-Fang Li; Yao Zhang; Jin-Lan Li; Xiao-Jun Huang; Guo-Rui Ruan (Apoptosis, 2009)

Identification of a novel rice bZIP-type transcription factor gene,OsbZIP1, involved in response to infection ofMagnaporthe grisea - Xiang-Bing Meng; Wen-Sheng Zhao; Rui-Ming Lin; Min Wang; You-Liang Peng (Plant Molecular Biology Reporter, 2005)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)